PHOSPHATE-SOLUBILIZING BACTERIA AND THEIR IMPACT ON THE GROWTH AND METABOLISM OF PISUM SATIVUM L. IN KODAIKANAL HILLS, TAMIL NADU. - U. Muthuvel; B., Harinathan; K., Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Compared with the other major nutrients, phosphorus is by far the least mobile and available to plants in most soil conditions. Although phosphorus is abundant in soils in both organic and inorganic forms, it is frequently a major or even the prime limiting factor for plant growth. To circumvent phosphorus deficiency, phosphate-solubilising bacteria (PSB) would play an important role in supplying phosphate to plants in a more environmentally-friendly and sustainable manner. The organisms with phosphate-solubilising potential will increase the availability of soluble phosphate and will enhance plant growth. In this present study, the phosphate solubilising microorganisms isolated from different soil samples from Kodaikanal Hills were identified on Pikovskaya agar plates with clear zone around the colonies. From the observation the strain-I and strain-II identified as Psedumonas aureginosa and Bacillus megaterium. Both strains showed higher than 180 (phosphate solubilisation efficiency), and reduced PH from 8.0 to below 6.0 indicates high phosphate solubilising efficiency, increased organic acid production. The influence of this phosphate solubilises on the growth and metabolism of Pea Plants were analysed. According to the results obtained from comparative field trial conducted in Kodaikanal Hills, use of PSB bio fertilizer shows marked difference in soil fertility, better performance in yield and yield related characteristics observed in the field of pea plants. (Pisum sativum L)